Approach to Patients with Increased Liver Biochemical and Function Tests : A Literature Review - Mustika, Syifa; Gersom, Camoya; Kongkam, Pradermchai (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
This review article provides a comprehensive examination of liver injury patterns, specifically focusing on hepatocellular and cholestatic patterns, and their respective diagnostic approaches. It highlights the importance of differentiating between these patterns through detailed clinical evaluations and the use of specific liver enzymes, including aminotransferases, bilirubin, alkaline phosphatase, gamma-glutamyl transpeptidase, 5'-nucleotidase, and lactate dehydrogenase. The review further explores liver function tests, such as albumin and prothrombin time, which are crucial in assessing liver function and guiding clinical management. A wide range of liver diseases is discussed, with a focus on those exhibiting hepatocellular patterns, such as viral hepatitis, acute liver failure, fatty liver disease (both alcoholic and non-alcoholic), and drug-induced liver injury (DILI), as well as other conditions like ischemic and autoimmune hepatitis. Cholestatic illnesses such as primary biliary cholangitis (PBC), primary sclerosing cholangitis (PSC), bile duct blockages, and genetic cholestatic syndromes are also investigated. This study seeks to improve physicians' and researchers' awareness of liver diseases, serve as a valuable resource for future research and teaching, and contribute to the improvement of diagnostic and therapeutic techniques in hepatology.Keywords : Cholestatic, hepatocellular, liver enzymes, liver functions